CRITICAL ARGUMENTS ABOUT READMISSION PRACTICES AND POLICIES BETWEEN EU AND TURKEY - Zühal Ünalp-çepel (Ankara Avrupa Çalışmaları Dergisi)
This paper aims to analyze the historical background and the recent developments concerning the Readmission Agreement and free visa negotiations between Turkey and the European Union through the official documents of Ministry for Foreign Affairs and the European Union. As a third view, the policies of Turkey and the EU will be critically assessed from the perspectives of the international governmental organizations and non-governmental actors, namely the United Nations, Human Rights Watch and Amnesty International through their regular reports. Within the scope of the analyses, it is aimed to discuss the critical arguments on political approaches and security policies of the European Union and Turkey on migration control and elaborate why both sides preferred to solve the migration crisis through regional, and specifically, bilateral instruments.